Computational study of YMg intermetallic. (2021) - Bhardwaj, Purvee; Jat, Vandna; Sanath Kumar, H.G.; Gupta, Sharad; Bhardwaj, Ramakant
Abstract: Exploration of binary YMg (CsCl) intermetallic is carried out by means of first principle calculation. YMg is stable in Cesium Chloride-type B2 structure at normal conditions. Basic possessions for instance interionic separation, modulus and its first derivative of pressure are reported. In electronic assets segment, band evaluation reveals the metallic character of YMg. Enthalpy calculations demonstrate that the same compound crystallizes in CsCl-type configuration. This technique can be functional for controlling of local optimizations based on first-principles calculations.